Study on Environment Correction Factor of Design Fatigue Curve Sample Problem and Strain Rate Calculation. (2015) - Shen, R.; He, Y.B.; Cao, M.
Abstract: Shanghai Nuclear Engineering Research and Design Institute (SNERDI) had been involved in ASME Section III environment assistant fatigue (EAF) task group (TG) and undertaken the calculation and verification work of first round sample problem, which was intended to test the engineering application of environmentally assisted fatigue (EAF) using the Fen correction factor method of Code Case N-792 Rev.0 and the proposed Code Case for evaluation of strain rate in EAF evaluations. This paper will present the sample problem of a light water reactor (LWR) primary loop stainless steel nozzle under some thermal transients and the calculation procedure of detailed integral methods according to Code Case N-792. Moreover, the method of strain rate calculation was particularly studied and discussed which is essential to the Fen value. The Fen correction factor results and the comparison with other participants is presented in this paper.